PENGARUH MODEL PEMBELAJARAN INKUIRI TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS PESERTA DIDIK KELAS XI MIPA SMAN 1 BONJOL - Annisa Fadhila (Jurnal Edukasi dan Penelitian Matematika, 2022)
Problem-solving ability is one of learning of mathematics purpose. But activities of learning are not optimal in facilitating students to increase their skills of problem-solving. The test results shown that the skills of problem-solving at SMAN 1 Bonjol is still low. One of the efforts to enhance students' skills of problem-solving is to apply the inquiry learning model. This study purpose was to reveal the effect of the inquiry model of learning on the skills of problem-solving in mathematical of the XI MIPA class students of SMAN 1 Bonjol. This research type was a quasi-experimental design with a nonequivalent posttest control group-only design. The population is all students of class XI MIPA. Sampling was conducted by simple random sampling of class XI MIPA 3 as the class for experimental and XI MIPA 4 as the class for control. The research instrument is consist of a problem-solving skills test. Based on the data analysis results obtained P-value = 0.008 where P-value <0.05. It can be concluded that the skills of problem-solving on students who study with the inquiry of model learning is better than students who learn with the learning on direct model in class XI MIPA SMAN 1 Bonjol. Keywords– , Direct Learning Model, Inquiry Learning Model, Problem Solving Ability, Quasi Experiment